POD PRODUCTION AND HYBRID SEED YIELD OBSERVED IN BREEDING GARDEN OF Acacia mangium x Acacia auriculiformis - Sri Sunarti (Jurnal Pemuliaan Tanaman Hutan, 2008)
Pod production and  hybrid seed yield were observed  in breeding garden of Acacia mangium x Acacia auriculiformis. The breeding garden was established in 2006 using 6 selected plus trees from first-generation progeny test of A. mangium and 12 selected plus trees from first-generation progeny test of A. auriculiformis.  Based on synchronisation in first phase flowering time (one year of age), there were 6 crossing combinations between A. mangium x A. auriculiformis. Twenty three (23) crosses were done with A. mangium as mother tree. Crosses were practiced by using about 2 spikes for each cross. In the first phase of flowering time, pod production and hybrid seed yield was still low with about 1.87 pod per spike and 2.05 good seeds per pod. This low production is probably due to the low intensity of flowering and lack of male flower in this first phase flowering. In addition, high incompatibility between pistil and pollen among the two different species also affected quality of seed in which about 1.54 seed per pod or 28,75% are poor hybrid seeds. Verification using seedling morphology indicated that almost all collected seed were hybrid seed. This finding showed that anther method without emasculation seemed to be effective to produce hybrid seed of A. mangium x A. auricuiliformis.